PENGARUH MINDFUL PARENTING TERHADAP KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK TRI INSANI PERMATA KOTA PEKANBARU - Salsabilla Zamzabil; Ria Novianti; Daviq Chairilsyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of mindful parenting on the independence of children aged 5-6 years at Tri Insani Permata Kindergarten, Pekanbaru City. The sample in this study were parents and children aged 5-6 years at Tri Insani Permata Kindergarten, totaling 41 children and parents. Data collection techniques used were questionnaires and observation sheets. Data analysis techniques used descriptive analysis, normality tests, homogeneity tests, linearity tests, and simple linear regression tests with the help of the IBM SPSS Statistics Ver. 25 program. From the results of the study, it is known that the level of mindful parenting is in the good category with a percentage of 77.41% and the level of independence is in the fairly good category with a percentage of 59.76%. Based on the results of the hypothesis test from the simple linear regression analysis, a correlation coefficient (R) value of 0.660 was obtained with a significance value of 0.000 <0.05, so that H₀ was rejected and Hₐ was accepted. This indicates that there is a significant influence between mindful parenting on the independence of children aged 5-6 years. Thus, it can be concluded that there is a positive and significant influence between mindful parenting on the independence of children aged 5-6 years at Tri Insani Permata Kindergarten, Pekanbaru City.